METAPHORICAL CONCEPTS IN TAYLOR SWIFT’S ALBUM FOLKLORE AND ALBUM EVERMORE - Yohanes Erick Laksono; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2023)
The aim of this research was to describe the metaphoricalconcepts of themetaphorical expressions in Taylor Swift’s album Folklore and album Evermore,and to analyze the similarities and differences between the metaphoricalconceptsin Taylor Swift’s album Folklore and those in album Evermore. This research wasqualitative. The data of the research were in the form of words, phrases, andclauses containing metaphorical concepts. The data collection technique was document analysis. The result of this research showed the most dominant metaphorical concepts are Happy is Up, Anger is Fire, Sad is Down, and Love is a Story. Some similarities in terms of metaphorical concepts were also found inthose two albums, namely Anger is Fire, Time is Money, Love is a Story, and Sad is Down. This research confirms the previous research that metaphor cannot be avoided and systemic, that orientational metaphors can be dominant in some researches, and that metaphors can be used to talk about a given topic in manyways.